(untitled) (Contemporary Journal of Social Science Review, 2026)
This study examines the impact of social media addiction on mindfulness, academic performance, and emotional exhaustion, while incorporating an Islamic perspective on moderation and self-regulation. Social media paradox theory, postulates excessive engagement with social media increase emotional exhaustion, thereby impairing mindfulness and academic outcomes. Empirically results show that Cronbach’s alpha value is 0.807. Furthermore, results indicate that social media escalate emotional exhaustion while academic performance negatively related with media addiction. It is also revealed by the finding, mindfulness is the most affected variable in selected variables of present study. Likewise, research provides evidence that over-use of social media negatively affects one’s ability to be mindful and mental health and academic achievement. To improve digital wellbeing in students, awareness programs regarding digital wellbeing, access to counseling, and implement mindfulness training programs, with ethical and spiritual development programs should be conducted in educational institutions.